SAT-191 A Case of Hypoplastic Left Heart Syndrome and Paraganglioma - Bowes, Christa (J Endocr Soc, 2020)
INTRODUCTION: Cyanotic heart disease and paragangliomas are two rare diagnosis. Co-occurrence of congenital cyanotic heart disease and pheochromocytomas/paragangliomas has been described, but the mechanism is unclear. In those patients where immediate cyanosis resulting from the congenital heart disease happens right after birth there is an association with an earlier detection of tumor compared to those with cyanotic heart disease later in life (26.6 years vs 46.3 years respectively) [1]. The objective of this case is to highlight this association, as a high degree of suspicion needs to be had when caring for individuals with cyanotic heart disease to pursue evaluation of these tumors. CASE: A 23-year-old man with a chief complaint of diffuse abdominal pain was found to have a 2.6 x 2.8 cm smoothly marginated soft tissue mass in the right lower quadrant on abdominal computed tomography. Patient had a known history of hypoplastic left heart syndrome (mitral atresia-aortic atresia) who had undergone a three-stage Norwood repair in childhood. In his adulthood was diagnosed with Central Adrenal Insufficiency, and Type 2 Diabetes Mellitus. At the time of presentation patient was short of breath, tachycardic (heart rate 115), and tender to palpation of his right lower quadrant. Plasma normetanephrines were 3.8 nmol/L (normal < 0.9 nmol/L), 24-hour urinary excretion of normetanephrine was 1117 mcg/24h (normal 103-390 mcg/24h). Plasma metanephrine levels were normal. A nuclear medicine whole body scan with metaiodobenzylguanidine (MIBG) scan confirmed a MIBG avid tumor in the right lower quadrant. Preoperative management was initiated with oral doxazosin. He underwent laparoscopic surgery with removal of a 3 cm pelvis mass resected from the retroperitoneal tissue deep to the peritoneum along the gonadal vein and ureter. Final pathology confirmed the diagnosis of a paraganglioma. Postoperatively, plasma normetanephrines were corrected at 0.86 nmol/L. Patient underwent genetic testing that was negative for FH, MAX, MEN1, NF1, RET, SDHA, SDHAF2, SDHB, SDHC, SDHD, TMEM127 and VHL. CONCLUSION: Multidisciplinary approach to these patients is essential given their complex hemodynamics. Long term follow up is necessary to monitor for tumor recurrence, review of case reports may suggest a higher risk of recurrence [1]. Of these case reports there has been no strong genetic association found, the most popular theory is a causal relationship from their cyanotic heart disease. References: Zhao B, Zhou Y, Zhao Y et al (2018) Co-occurrence of pheochromocytoma-paraganglioma and cyanotic congenital heart disease: A case report and literature review. Front Endocrinol. https://doi.org/10.3389/fendo.2018.00165